The Preparation and Performances of Self-Dispersed Nanomicron Emulsified Wax Solid Lubricant Ewax for Drilling Fluids - Feng-shan Zhou; Ting-ting Wang; Zheng-qiang Xiong; Wen-yue Guo; Xi Xiang; Huan-na Wang; Xia-lei Zhu; Fang Liu; Bao-lin Cui (Journal of Spectroscopy)
An oil-in-water nanomicron wax emulsion with oil phase content 45 wt% was prepared by using the emulsifying method of surfactant-in-oil. The optimum prepared condition is 85°C, 20 min, and 5 wt% complex emulsifiers. Then the abovementioned nanomicron emulsifying wax was immersed into a special water-soluble polymer in a certain percentage by the semidry technology. At last, a solidified self-dispersed nanomicron emulsified wax named as Ewax, a kind of solid lubricant for water based drilling fluid, was obtained after dried in the special soluble polymer containing emulsifying wax in low temperature. It is shown that the adhesion coefficient reduced rate (ΔKf) is 73.5% and the extreme pressure (E-P) friction coefficient reduced rate (Δf) is 77.6% when the produced Ewax sample was added to fresh water based drilling fluid at dosage 1.0 wt%. In comparison with other normal similar liquid products, Ewax not only has better performances of lubrication, filtration loss control property, heat resistance, and tolerance to salt and is environmentally friendly, but also can solve the problems of freezing in the winter and poor storage stability of liquid wax emulsion in oilfield applications.